Application of in-line high shear mixing process in the oxidative-adsorptive desulfurization of diesel fuel - Dayrit, Raymond Ayson (2013)
The removal of sulfur from diesel fuel has attracted the attention of many researchers due to the more stringent regulations imposed on the allowable sulfur content of diesel in may countries. Environmental regulations in the Philippines have set the allowable sulfur content of diesel to less than 50 ppm by 2016. Oxidation using in-line mixing followed by adsorption is a promising desulfurization technology than can be explored. This paper presents the results of experimental investigations of oxidative desulfurization of diesel fuel using continuous high-shear mixing CSTR and in-line mising set-ups. Alumina was used for fixed-bed adsorption of oxidized sulfur compounds. The effects oxidation parameters namely reaction temperature, high shear mixing speed, diesel flow rate on sulfur removal were investigated. At 82% sulfur removal, in-line mixing flow rate was 500 ml/min while CSTR flow rate was 360 ml/ 30 min (12 ml/min). Optimal oxidation operating parameters using Box-Behnken Design were 18000 rpm high shear mixing speed, 500 ml per min of diesel and 300 ml per min of hydrogen peroxide. Increasing the amount of adsorbent alumina from 5 to 15 g decreases the residual sulfur in diesel fuel from 265 to 30 ppm at 70°C. In this study, the sulfur content of diesel fuel was reduced from 1480.4 ppm to 30 ppm which is well within the limit of 50 ppm for Euro IV standard.
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman
Keywords: Desulfurization; Diesel fuels; Adsorption